TOKSISITAS EKSTRAK TERPURIFIKASI DAUN PULUTAN (Urena lobata L.) FRAKSI ETANOL TERHADAP MORTALITAS LARVA NYAMUK Aedes Aegypti - Indah Atika Amalia; Dwi Wahyuni; Kamalia Fikri (saintifika, 2021)
Dengue hemorrhagic fever (DHF) is a disease that is a major public health problem throughout the world. Indonesia is one of the countries with the largest dengue cases in the world. One of the largest dengue cases in Indonesia is in East Java Province whic h reached 5,733 cases. Dengue fever is transmitted to humans through the Aedes aegypti mosquito infected with the dengue virus. The way to control DHF is to control the vector, namely by breaking the mosquito life cycle using selective and safe biological larvicides. Plants that have potential as biological larvicides are pulutan ( Urena lobata L.) especially the leaves. Pulutan leaves are used as biological larvicides through an extract purification process. This study aims to determine the toxicity of puri fied extract of pulutan leaf ( Urena lobata L.) ethanol fraction on mortality of Aedes aegypti mosquito larvae. Toxicity based on WHO standard (2002), was determined by LC 50 of purified extract of pulutan leaf ethanol fraction on mortality of Aedes aegypti mosquito larvae. Results Based on probit analysis using the Minitab 14 application software, the LC 50 value was 905,36 5 ppm with a lower limit of 810 , 626 ppm and an upper limit o f 992 , 277 ppm. According to this study, purified extract of pulutan leaf ethanol fraction was toxic to Aedes aegypti mosquito larvae and had a larvicidal effect